Impact of short term yoga on anthropometric measures, body composition and serum lipid profile in overweight and obese adults: a pilot study - Shetty, Balakrishna; Shetty, Geetha B.; Shantaram, Manjula; K., Manjunath N. (International Journal of Research in Medical Sciences, 2018)
Background: Excess bodyweight is the sixth most important risk factor contributing to the overall burden of disease worldwide. Overweight and obesity have been called a global epidemic by the World Health Organization. The epidemic reflects progressive decreases in physical activity, together with substantial dietary changes with passive over-consumption of energy despite the neurobiological processes controlling food intake. This pilot study was undertaken to find out the impact of yoga practice in overweight and obese individuals. Methods: total of 32 subjects with BMI, ≥23to ≤40 were selected for the study for a single group pre-post trial. The subjects had undergone yogic intervention for one hour in the morning for 10 days. The changes in anthropometric measures, body composition and serum lipid profile were assessed before and after 10 days of yoga therapy. Results: The data obtained was verified for normal distribution and analysed using paired t-test with SPSS (version 20.0) package. Significant decrease in body weight, BMI, triglycerides and total cholesterol in obese subjects and a significant decrease in body weight, BMI and triglycerides of overweight subjects was observed. Conclusions: The study demonstrates the efficacy of yogic practices on anthropometric measures and lipid profile subjects with overweight and obesity.